Strengthening Interreligious Communication: An Analysis of Interfaith Greetings in Fazlur Rahman's Hermeneutics of Hadith - Minhad Ali Yahya; Akhmad Rifa’i (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Interfaith greetings in Islamic law have become a significant issue in multicultural societies. Classical fiqh discusses the boundaries of interreligious interaction, yet Islamic law is inherently dynamic and adapts to the evolution of society. This study addresses two main aspects. First, it explores Fazlur Rahman’s concept of hadith and Islamic law, emphasizing the importance of ijtihad in responding to contemporary challenges. Second, it analyzes hadiths related to the prohibition of tasyabbuh (imitation), which some scholars use as a basis to avoid interfaith greetings. The research employs a qualitative method with a library research approach. The findings highlight the importance of understanding social context and intention when interpreting Islamic law concerning interfaith greetings. Fazlur Rahman advocates for an inclusive approach that aligns Islamic law with the realities of modern society. Regarding the hadith on tasyabbuh, there are varying scholarly interpretations, necessitating a deeper understanding and the application of principles of tolerance. The study concludes by emphasizing the need to align Islamic law with humanitarian values and peace without compromising the sanctity of religious teachings. Interfaith greetings can serve as an expression of respect and a means to strengthen harmony in society. A dialogical approach that values diversity and inclusivity is key to resolving this dilemma. This research is expected to contribute positively to understanding and practicing interfaith tolerance in heterogeneous societies.